Novel approach in control release monitoring of protein-based bioactive substances from injectable PLGA-PEG-PLGA hydrogel - Klara Lysakova; Kristyna Hlinakova; Katerina Kutalkova; Radka Chaloupkova; Jan Zidek; Jana Brtnikova; Lucy Vojtova (eXPRESS Polymer Letters, 2022)
In recent times, autologous fat grafting has emerged as one of the most popular techniques for restoring volume depletion. Although the retention predictability of grafted fat has been improved, the quality of grafted tissue is still unsatisfactory. Unpredictable volume loss and low-fat survival is a major problem after application. Biodegradable PLGA-PEGPLGA (poly(lactic-co-glycolic acid)-b-poly(ethylene glycol)-b-poly(lactic-co-glycolic acid)) hydrogel delivery system enriched with stable fibroblast growth factor 2 (FGF2-STAB®), due to its properties, seems to be attractive material that will help to increase fat life. In this study, the mechanism of FGF2-STAB® release from an injectable thermosensitive and biodegradable PLGA-PEG-PLGA hydrogel was monitored. First-order kinetics were controlled mainly by decreasing the concentration of an active compound in the matrix and, at a later stage, by matrix degradation. Furthermore, the activity of the protein after release from the hydrogel matrix was studied. No loss of FGF2-STAB® activity in the dynamic system after 14 days has been detected. The development of such a drug delivery system appears promising for further use in reconstructive medicine e.g., in mixing with fat graft being the subject of current research.